Interstitial oxygen related defects and nanovoids in Au implanted a-SiO2 glass depth profiled by positron annihilation spectroscopy. (12th November 2015) - Ravelli, L; Macchi, C; Mariazzi, S; Mazzoldi, P; Egger, W; Hugenschmidt, C; Somoza, A; Brusa, R S
Abstract: Samples of amorphous silica were implanted with Au ions at an energy of 190 keV and fluences of ions cm −2 and ions cm −2 at room temperature. The damage produced by ion implantation and its evolution with the thermal treatment at 800 °C for one hour in nitrogen atmosphere was depth profiled using three positron annihilation techniques: Doppler broadening spectroscopy, positron annihilation lifetime spectroscopy and coincidence Doppler broadening spectroscopy. Around the ion projected range of nm, a size reduction of the silica matrix intrinsic nanovoids points out a local densification of the material. Oxygen related defects were found to be present at depths four times the ion projected range, showing a high mobility of oxygen molecules from the densified and stressed region towards the bulk. The 800 °C thermal treatment leads to a recovery of the silica intrinsic nanovoids only in the deeper damaged region and the defect distribution, probed by positrons, shrinks around the ion projected range where the Au atoms aggregate. Open volume defects at the interface between Au and the amorphous matrix were evidenced in both the as implanted and in the thermal treated samples. A practically complete disappearance of the intrinsic nanovoids was observed around when the implantation fluence was increased by two orders of magnitude ( ions cm −2 ). In this case, the oxygen defects move to a depth five times larger than .